KELAYAKAN SISTEM SALURAN DRAINASE MENINJAU SUPPLY DAN DEMAND UNTUK MENDUKUNG RENCANA KAWASAN PERKOTAAN PRINGSEWU - Fatmawati Hajar Aswad; Lutfi Setianingrum (Jurnal Perencanaan dan Pengembangan Kebijakan, 2021)
Pringsewu Regency is a district that is currently focusing on the preparation and maturation of the 2011-2031 Regional Spatial Plan, which includes a plan to prepare it to become an urban area. In order to have good city management, it's therefore, necessary to study the feasibility of the drainage system which later can be used as input for careful planning to support the Pringsewu Urban Area plan by paying attention to the availability and quantity of drainage channels so as not to cause a disaster problem in the future. Based on the results of the analysis that has been carried out that the capacity of the drainage channel, namely Qtotal> Qsaluran, so that the channel cannot accommodate rainwater and wastewater, so to support the Pringsewu Urban Area, the drainage channel is currently not feasible to support the Pringsewu Urban Area plan when viewed from an infrastructure perspective, namely existing drainage system. Keywords: Drainage, Urban Area.